Pollution from Aircraft Emissions in the North Atlantic Flight Corridor: Overview on the POLINAT Projects - Schumann, U.; Schlager, H.; Arnold, F.; Ovarlez, J.; Kelder, H.; Hov, O.; Hayman, G.; Isaksen, I.S.A.; Staehelin, J.; Whitefield, P.D. (2000)
The Pollution From Aircraft Emissions in the North Atlantic Flight Corridor (POLINAT) projects were undertaken to investigate the impact of aircraft engine exhaust emissions on the state of the atmosphere in the North Atlantic flight corridor. Changes in the composition of the lower stratosphere and upper troposphere from aircraft emissions are identified from combined measurements and model analyses. Measurements were performed using the Deutsches Zentrum für Luft- und Raumfahrt Falcon research aircraft and a Swissair B-747 over the North Atlantic covering the altitude range 6 to 13 km in November 1994 and June/July 1995 and from August to November 1997. The measurements include those of nitrogen oxides, nitrous and nitric acids, sulfur dioxide, sulfuric acid, acetone, carbon dioxide, ozone, water vapor, carbon monoxide, aerosols, and meteorological parameters. The atmospheric composition was found to be highly variable, and emissions from sources at the surface or from lightning discharges also contribute strongly to the nitrogen oxides abundance and ozone formation. Contributions from aircraft emissions have been measured and identified in single and multiple plumes of several hours ages, and accumulation of such nitrogen oxides and particles emissions can be identified under certain conditions in and downstream of the flight corridor region. Acetone was found at high mixing ratios. The global and regional models predict ozone increases of 3 to 6% by current air traffic at the flight corridor altitude north of 30°N, in agreement with previous model analyses but too small to be measurable. In autumn, the upper troposphere is often humid with water vapor concentration far above ice saturation, providing conditions for persistent contrails.